Frequency of Musculosketelal Problems in Beauticians of Rawalpindi and Islamabad - Huda Anjum, Wardah Qazi, Hadiya Rehman, Muhammad Saad Shafique, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Many factors affect patient adherence to physical therapy treatment like unavailability of space and tools, lack of funding and awareness etc. Recognition of these barriers may help the physiotherapists to overcome these hurdles and ultimately improve treatment outcomes. The purpose of this study was to determine common MSK problems in beauticians, to identify the cause of MSK disorders, common spine deformity and awareness level of physical therapy among beauticians. Methodology: A descriptive cross-sectional survey was conducted using a self-structured questionnaire which was generated after literature review. 300 beauticians were considered for data collection. Result: Our study revealed that 59.9% of beauticians were having back pain,66% of them were having pain due to prolonged standing,49.3% of them were having normal posture,21.8% were having hyperextended knee and only 19% of them were aware of physical therapy treatment. Conclusion: It is concluded that the presence of back pain due to prolong standing was evident in beauticians. The most common MSK postural problem was found to be rounded shoulder. The awareness of physical therapy amongst beauticians was less evident and those who were aware were also not consulting physical therapists for their MSK problems. Keywords: beauticians, MSDs, posture, work-related disorders, musculoskeletal system.